Role-Playing Improves Speaking Proficiency Skills - Katemba, Caroline V.; Grace, Ruth M. (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2023)
The goal of this research is to determine whether the Role Play Technique may improve students' speaking skills, particularly in grade XI. The study was carried out at SMAN 1 Cisarua, Bandung Barat, with 34 students from grade XI Science-3 serving as the sample. This is a pre-experimental study. After 16 hours of treatment (two hours per meeting utilizing the Role Play technique), the students were given a pre-test and a post-test. After analyzing the data, it was discovered that there is a substantial difference in enhancing students' speaking skills following therapy with the Role Play Technique. Based on the interpretation of the data analyzed it was found that the p-value is 0.000 (Sig.) ≤ α (0.05) then Ha is accepted and Ho is rejected. The pre-test score is 42,08 % and the post-test score is 62,6 %. And the gain is 0,377. It is recommended to keep motivating the students to use the role-play properly in the future to improve their English speaking skills.